The Yeast Synaptojanin-like Proteins Control the Cellular Distribution of Phosphatidylinositol (4,5)-Bisphosphate - Stefan, Christopher J. (The American Society for Cell Biology, 2002)
Phosphoinositides (PI) are synthesized and turned over by specific kinases, phosphatases, and lipases that ensure the proper localization of discrete PI isoforms at distinct membranes. We analyzed the role of the yeast synaptojanin-like proteins using a strain that expressed only a temperature-conditional allele of SJL2. Our analysis demonstrated that inactivation of the yeast synaptojanins leads to increased cellular levels of phosphatidylinositol (3,5)-bisphosphate and phosphatidylinositol (4,5)-bisphosphate (PtdIns(4,5)P(2)), accompanied by defects in actin organization, endocytosis, and clathrin-mediated sorting between the Golgi and endosomes. The phenotypes observed in synaptojanin-deficient cells correlated with accumulation of PtdIns(4,5)P(2), because these effects were rescued by mutations in MSS4 or a mutant form of Sjl2p that harbors only PI 5-phosphatase activity. We utilized green fluorescent protein-pleckstrin homology domain chimeras (termed FLAREs for fluorescent lipid-associated reporters) with distinct PI-binding specificities to visualize pools of PtdIns(4,5)P(2) and phosphatidylinositol 4-phosphate in yeast. PtdIns(4,5)P(2) localized to the plasma membrane in a manner dependent on Mss4p activity. On inactivation of the yeast synaptojanins, PtdIns(4,5)P(2) accumulated in intracellular compartments, as well as the cell surface. In contrast, phosphatidylinositol 4-phosphate generated by Pik1p localized in intracellular compartments. Taken together, our results demonstrate that the yeast synaptojanins control the localization of PtdIns(4,5)P(2) in vivo and provide further evidence for the compartmentalization of different PI species.